Financial Performance and Club Success in the English Premier League - Rahmadina, Aulia Musvita; Bhilawa, Loggar (AFEBI Accounting Review, 2025)
This study investigates the business impact of financial performance on the competitive success of football clubs in the English Premier League (EPL) during the 2016/2017 to 2022/2023 seasons. Recognizing that strategic financial management is critical for sustainable club growth and market competitiveness, this research adopts a quantitative explanatory approach. Using secondary financial data, it applies descriptive statistics, multiple linear regression, and hypothesis testing (T-test, F-test, and R²) to examine how key financial indicators: profitability (ROA, ROE), liquidity (CR), and leverage (DER) influence club performance on and off the pitch. The findings reveal that effective asset utilization (ROA) and liquidity management (CR) significantly drive club success, highlighting the importance of financial health in operational decision-making and competitive positioning. Meanwhile, profitability measured by ROE and leverage ratios showed no statistically significant effects. This study offers practical insights for club management and stakeholders on prioritizing financial strategies to optimize financial sustainability and sporting achievements, strengthening the business foundations of EPL clubs.